Implementation of Student Centered Approach (SCA) with Station Rotation Learning Model to Support 21st Century Learning - Ervan Dwi Yuliaristiawan; Henry Praherdhiono; Ence Surahman (Dinasti Publisher, 2025)
The Student-Centered Approach (SCA) is the basis for designing learning to equip learners with 21st century skills. One model that supports SCA is Station Rotation, which allows personalization of learning by dividing the class into stations with different activities. This research uses a systematic review of studies to analyze the impact of implementing Station Rotation in classroom learning. The results show that this model positively contributes to students' cognitive learning outcomes, critical thinking skills, collaboration, and learning motivation. This model can be applied at various levels of education, but needs to be combined with other learning strategies to be more optimal.